Antidepressant-like effects of Xiaochaihutang in perimenopausal mice. (10th February 2020) - Zhang, Kuo; Wang, Zhiqian; Pan, Xing; Yang, Jingyu; Wu, Chunfu
Abstract: Ethnopharmacological relevance: Xiaochaihutang (XCHT) is a traditional Chinese medicine prescription for thousand years in China. Our previous researches show that XCHT has antidepressant-like effects in several depression models, but effect and mechanism of XCHT in perimenopausal depression are still vague. Aim of the study: To reveal the antidepressant-like effect and mechanism of XCHT in perimenopausal mice. Materials and methods: Perimenopausal depression model is executed by ovariectomy combined with chronic unpredictable mild stress (OVX-CUMS). Tail suspension test (TST), forced swim test (FST), elevated plus-maze (EPM), novelty suppressed feeding (NSF) and locomotor activity are used to assess antidepressant-like effects of XCHT. The Level of estradiol (E2 ), follicle-stimulating hormone (FSH), gonadotrophin releasing hormone (GnRH), corticosterone (CORT), adrenocorticotrophic hormone (ACTH) and corticotropin releasing hormone (CRH) are evaluated by ELISA. Antidepressant mechanisms of XCHT in OVX-CUMS mice are analyzed by 5-hydroxytryptamine (5-HT), tryptophan hydroxylase 2 (TPH2) and estrogen receptor α and β (ERα/β). Results: The results show that OVX-CUMS significantly increases the immobility time in TST and FST, increases latency to feed, decreases food consumption in NSF and both the time spend and number of entries in open arms in EPM. While, oral administration of XCHT can significantly normalize above depression-like behaviors in OVX-CUMS mice. Moreover, XCHT also remarkably normalized levels of 5-HT, 5-HIAA, E2, GnRH, CORT, ACTH and CRH in OVX-CUMS mice. Finally, the expression of ERβ and TPH2 are decreased by OVX-CUMS in prefrontal cortex and hypothalamus, and XCHT can restore these decrease. Conclusion: Current findings suggest XCHT can alleviate perimenopausal depression-like behaviors, restore 5-HT and hormones in OVX-CUMS mice, which may be related to normalizing the functions of HPA/HPO axis and enhancing expression of ERβ and TPH2 in prefrontal cortex and hypothalamus. Graphical abstract: Image 1